The Birth of the Liberal Society - Dan Usher (Queen's University, Department of Economics, 1990)
The liberal society might be supposed to have emerged directly from anarchy, spontaneously or in a social contract; or the liberal society might be supposed to have emerged indirectly by a roundabout process in which anarchy gave way in the first instance to despotism and then despotism gave way to a liberal society. The liberal society, for the purposes of this paper, is a society with an economy based on private property and with a polity based on majority rule voting. Anarchy is a society without law or government in which people divide their time among production, defending what they have produced and taking goods form others. Despotism is a society with a ruling class that exploits the rest of the population as a shepherd exploits a flock of sheep. It makes more sense to suppose that the liberal society evolved by the indirect route through despotism than to suppose that it evolved directly out of anarchy.
Keywords: 330